"This State Is Racist . . ": Policy Problematization and Undocumented Youth Experiences in the New Latino South. (September 2017) - Rodriguez, Sophia; Monreal, Timothy
This article examines how state-level policy discourse articulates a category of knowledge about immigrants in South Carolina that governs the everyday experiences of undocumented immigrants. In the analysis of proposed and enacted immigration legislation from 2005 to the present, we use a Foucauldian-inspired critical discourse analysis to better understand how policy forms out of a problematization of marginalized groups such as undocumented immigrants. We find that policy constitutes immigrants as an economic and security threat and as Othered, outsiders to the state. This allows for policy makers to propose seemingly rational solutions such as "proving one's status" and "increased law enforcement." We suggest that this categorization of knowledge about immigrants has clear implications for educational attainment, social mobility, and public life while highlighting the viability of a Foucauldian-inspired theorization of discourse and critical discourse analysis as a method for inquiry.